Prevalence and molecular characterization of β-lactamase producers and fluoroquinolone resistant clinical isolates from North East India - Bipasa Kar; Mohan Sharma; Annalisha Peter; Pankaj Chetia; Bijoy Neog; Amrit Borah; Sanghamitra Pati; Debdutta Bhattacharya (Elsevier, 2021)
Introduction: The rapid emergence and variations of antibiotic resistance among common gram negative bacteria cause a significant concern specially in India and all over the world because of high mortality and morbidity rates. Methods: In our study, we screened 189 bacterial isolates from Assam Medical College & Hospital, Dibrugarh for antibiotic resistance pattern and tried to identify the resistant genes causing responsible for β-lactam and fluoroquinolones resistance. Results: More than 80% and 45% strains were resistant to all the 3rd generation cephalosporins, fluoroquinolones respectively. Among the 3rd generation cephalosporin resistant strains, 38% and 24% isolates were only ESBL and MBL producers respectively and 11% were reported to have both ESBL and MBL genes. The ESBL positive isolates have shown the dominance of CTX-M3 gene. VIM-1 gene was mostly reported in MBL producers. Our study probably for the first time reporting SIM-1 and SPM-1 MBL gene from India. Mutations in QRDR is found to be the primary cause of fluoroquinolone resistance along with efflux pump and PMQR presence. Conclusion: The study represents the first detailed study on antibiotic resistance from NE India this could help to take control measures for the emerging antibiotic resistance in hospital and community based infections in North East India.